Peningkatan Kualitas Hidup Pasien Stroke melalui Edukasi Terapi Wicara dan Stroke Home Care - Sukmawati, Sukmawati; Mamuroh, Lilis; Nurhakim, Furkon (GUYUB: Journal of Community Engagement, 2024)
Common problems experienced by stroke patients include brain disorders, resulting in limb weakness and impaired focal nerve function, including speech disorders. The family plays a crucial role in the patient's rehabilitation process; therefore, they need to enhance their understanding of speech therapy and home care for stroke patients. This community service aims to increase family knowledge regarding speech therapy and home care. Methods employed in this service include lectures, question-and-answer sessions, and interactive discussions. Participants consisted of 23 families of stroke patients treated at Garut Hospital. The results of this service demonstrated that health education effectively increased participants' knowledge about speech therapy and home care for stroke patients. Prior to the service, 17.4% had good knowledge, with an average score of 68.39. After participating in the service, 100% of participants demonstrated good knowledge, with the average score increasing to 85.43. The study found a significant positive effect of education on speech therapy and home care knowledge among participants, with a p-value of 0.001.